Changes in wine consumption and its impact on the Spanish cooperative wineries, 1955-2010 - Medina Albaladejo, Francisco (Cuyonomics. Investigaciones en Economía Regional, 2017)
The wine sector has undergone a significant transformation during the twentieth century, especially in the second half, in terms of both supply and demand. The habits and preferences of consumers have changed dramatically, which is one of the main reasons behind the transformations of the sector. This paper aims to examine the effects of these new habits on the Spanish wine sector, especially with regard to the production and marketing processes. Especial focus will be put on a particular kind of firm, cooperatives, which are of enormous importance for the Spanish wine industry.